ANALISIS QUALITY ASSURANCE INSTALASI GAWAT DARURAT DI RUMAH SAKIT SIMPANGAN DEPOK TAHUN 2022 - Ni Putu Ayu Larassasti (2023)
Every hospital must be able to provide optimal healthcare service regarding the regulation Kepmenkes No. 129 of 2008 about Minimum Service Standards of Hospital. The ER unit plays an important role in an emergency where fast action is required. The number of visits to the ER at RS Simpangan Depok increases every month, so it is important for the hospital to carry out services according to the standards. This study aims to see an overview of the implementation of Minimum Service Standards in the Emergency Room. This study used a descriptive method with a qualitative approach. Data collection was carried out through in-depth interviews, observation, and document review. The data analysis was using triangulation techniques. The results of this study found that the implementation of MSS in the ER was not yet optimal. Lifesaving ability for children and adults are 100%, emergency service opening hours are 24 hours, emergency service providers are certified at 93%, one disaster management team is available, doctor's response time is 4.6 minutes, patient death ≤ 24 hours is 1.4 deaths per thousand people, there is no obligation for patients to pay a down payment is 100%, and patient satisfaction reaches 69.96%. However, sometimes the response times exceeding 5 minutes and deaths ≤ 24 hours > 2 per thousand. This study can be used by the hospital as an evaluation material in improving service quality regarding the national standards, especially in the emergency room unit.